Analysis of the quality of service youtube video streaming on the wireless network of the Faculty of Engineering Universitas Muhammadiyah Bengkulu - Bagus Daru Irawan; Cahyo Prihantoro (Borobudur Informatics Review, 2021)
This study aims to determine how good the quality of the wireless network at the Faculty of Engineering, Muhammadiyah Bengkulu University on Youtube Video Streaming services using the QoS (Quality of Service) parameter. This research is a quantitative research which refers to the research method according to Polit DF and Hungler BP. The research was carried out by monitoring the Youtube Video Streaming service on the UM GEDUNG G2 Wi-Fi network at the Faculty of Engineering, University of Muhammadiyah Bengkulu which was designated as a sample of data on each service. Streaming Youtube Videos at 360p, 480p and 720p video quality, using Wireshark Software. Data collection techniques used were observation, interviews and from journal sources related to this study. From the results of the research carried out it can be concluded that the results of the Throughput on the Youtube 360p Streaming Video service obtained an overall average result of 665Kbps in the TIPHON category including bad, while the overall results of the average value of Package loss, Delay and Jitter are included in the very good category. and good, as well as Youtube Video Streaming services 480p and 720p get an average value - the overall average on Throuhput, Package loss, Delay and Jitter are included in the good and very good categories according to the TIPHON version.